Корпусна лінгвістика: історія формування і перспективи розвитку - Войтко, Галина Богданівна; Voitko, H. B. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано основні етапи розвитку та становлення корпусної лінгвістики як складової час¬тини прикладної лінгвістики. Розглянуто основні корпуси текстів і їх характеристики, простежено вплив електронних корпусів на подальший розвиток лінгвістичних досліджень. На сучасному етапі розвитку лінгвіс¬тики застосування електронного корпусу текстів стало невід’ємним складником багатьох галузей мовознавства та суміжних дисциплін. The paper analyzes the main stages of development and establishment of corpus linguistics as the integral part of applied linguistics, since the creation and usage of corpus opens up new possibilities and perspectives for the analysis of linguistic material and the use of corpus for educational purposes. Definitions of such terms as corpus linguistics, corpus are considered. The article outlines main problems and goals of corpus linguistics. The characteristics of corpora and the impact of the emergence of electronic corpus for further development of linguistic research are described. Special attention is given to the description of corpora that were created beginning with corpus linguistics establishment. Today electronic corpora are an integral part of linguistic research, as allow exploring large amounts of information to obtain accurate data and use corpora for educational purposes. At the present stage of linguistic research corpora have become an integral part of many branches of linguistics and related disciplines.
Corpus Linguistics: the History of Formation and Development Prospects
Keywords: корпусна лінгвістика; corpus linguistics; корпус; corpus; породжувальна граматика; generative grammar